Producing society or the self-producing of society? A study of an NGO's difficult situation on poverty reduction. (January 2018) - Sun, Feiyu; Chu, Huijuan; Zhang, Yanlong
How social organizations that envision social reforms interact with existing social and political structures in their practice is key to the understanding of philanthropic organizations and their social actions in the current Chinese context. To address this issue, a 'social production' perspective was adopted and the structural features and poverty alleviation practices of a philanthropic organization, which has successfully solved the entry problem whilst clearly recognizing and maintaining its independence, were studied. The organization, with a clear vision, actionable goals, compatible and strict management as well as monitoring systems, has encountered many obstacles that are inconsistent with its goals. The organization may thus be unable to realize its goals in practice, may fall into a detached state, and even become a structural space for the reproduction of local society. This paper attempts to provide an understanding of the obstacles that this organization encountered from a 'state–society' perspective and study it by re-embedding the organization into the local social–political context. It is argued that this organization became an academically interesting entity because it illustrates the complexity of the transition process of Chinese society and provides for observation of the society's self-reproduction process. Thus the various social realities and problems observed from this organization's practices and actions can be seen as analogous to China's current political and social issues; as such it can therefore help with developing a holistic understanding of the phenomena, mechanisms and issues in China's political and social transition process.